Innovative Interventions with Alcohol Problems in Rural Areas: An Indian Experience and its Relevance to Rural America - Kala Chakradhar (Social Work and Society)
Conventional interventions used to address the complex problems of substance abuse call for multifaceted approaches reflecting the diverse backgrounds of affected populations.  In this paper the rural context is highlighted as an asset in contributing to sustainable recovery from alcohol problems. Against the background of comparing two international rural contexts and recognizing shared identities, a case is made for transfer of knowledge east to west.  The success elements of a unique approach to intervention with problems associated with excessive drinking in rural areas of South India, based on the experiences of Community-Based Rehabilitation camps is described.  Spanning two decades of systematic implementation, the camps utilize existing community resources for planning, execution, and follow-up of treatment while simultaneously creating greater awareness about alcohol abuse through community education.  After a critical examination of prevailing treatment options for problem drinking in rural America, inter-country analysis reveals contextual similarities between rural America and rural South India based on community-orientation, cost-containment, and social capital formation with implications for rural social work intervention with alcohol problems in the United States.